Teaching Narrative Text By Using Brainwriting Learning Model - Lisanty, Fibri Indira; Sri Rahayu; Nur Tanti Aulia (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2023)
The purpose of this research is to prove effectivenes of brainwriting learning model in teaching student writing, especially narrative text. This research used pre-experimental method. The population of this research was grade 3 students of UPT SMA NEGERI 5 LUWU TIMUR which was consisted of 3 classes, each class consisted 30-33 students. This research used purposive sampling. The sample of this research was 30 students of class XII MIA 1 and XII MIA 2. This research used SPSS 20 to analyze the data. The data was taken by used test. The result of this research showed that used Brainwriting Learning Model in teaching narrative text can improve students' narrative text skills. This is evidenced by seeing a significant difference between the mean scores of students in the pre-test and post-test. In the pre-test the mean score of the students was 42.23 and the mean score of the post-test was 63.67, it means that there was a significant increase between the pre-test and the post-test. The standard deviation of the pre-test value is 12.339 and the standard deviation of the post-test is 9.007. This shows that the mean post-test score is higher than the pre-test after treatment (42.23> 63.67). Then the significant test value of the T-test of 0.000 is calculated using SPSS, and the results of statistical analysis for the significant level (α) = 0.05 therefore the probability results are 0.000 <0.05, then H0 is rejected and H1 is accepted, it means that there is a significant increase between the pre-test and post-test results of students in narrative text using brainwriting learning model.